Asmaul Husna: Studi Peningkatan Hasil Belajar Siswa Materi Teladan Mulia menggunakan Media Audio Visual - Yulinda, Yulinda (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Introducing Asmaul Husna to elementary school students is important and can be done through surrounding learning themes that can lead students to the problem-solving process. The underlying reason for the importance of Asmaul Husna is that it is part of a possible learning model that can help students in recognizing God. This type of research is Classroom Action Research. This research was conducted at SD Negeri 111 Bengkul Selatan, the subjects of this research were grade IV students totaling 20 students. Data analysis using the results of the observation sheet has been filled in by the observer to see the suitability of the action plan. The results revealed that the completion of student learning outcomes through audio-visual learning had a positive impact in improving student learning outcomes. The conclusion of the research found that the use of audio-visual media in learning activities on the material of noble examples of asmaul husna can improve student learning outcomes, it can be seen that the completeness of student learning outcomes through audio-visual learning has a positive impact in improving student learning outcomes. This can be seen from the more stable understanding of students of the material presented by the teacher (learning completeness increases from cycle I, II and III).